Recent progress in MgB2 superconducting joint technology - Hao Liang; Dipak Patel; Mahboobeh Shahbazi; Andrzej Morawski; Daniel Gajda; Matt Rindfleisch; Richard Taylor; Yusuke Yamauchi; Md Shahriar A. Hossain (Journal of Magnesium and Alloys, 2023)
Magnesium diboride (MgB2) magnets have the potential to be the next-generation liquid-helium-free magnet for magnetic resonance imaging (MRI) application due to their relatively high superconducting transition temperature, high current density and low raw material cost compared with current commercial niobium-titanium (Nb-Ti) magnets. A typical superconducting magnet includes several coils. To produce an ultra-stable magnetic field for imaging in MRI, a superconducting electromagnet operating in a persistent mode is crucial. Superconducting coils of the electromagnet in MRI are short-circuited to operate in the persistent mode by connecting coils with superconducting joints. Persistent joints have been demonstrated for in-situ and ex-situ wires of both mono- and multi-filamentary structures, made predominantly by PIT techniques similar to those used in wire production. To realise further engagement of MgB2 in MRI applications, enhancing the performance of MgB2 superconducting joints is essential. This literature review summarises research and development on MgB2 superconducting joining technology.